Analysis of Digital Literacy Needs as the Main Foundation in Education for Sustainable Development (ESD) - Erna Noor Savitri; Sudarmin Sudarmin; Murbangun Nuswowati; Sigit Saptono; Arif Billah (Jurnal Pemberdayaan Masyarakat, 2025)
Digital literacy is critical in supporting Education for Sustainable Development (ESD) by providing access to information, raising awareness, and encouraging engagement with environmental, social, and economic issues through technology. As part of 21st-century skills, digital literacy empowers educators and learners to utilize digital platforms for interactive and practical learning while fostering critical thinking, collaboration, communication, and creativity to address sustainability challenges. Digital literacy also supports innovation in sustainable practices such as renewable energy, precision agriculture, and responsible resource management. This study aims to analyze the digital literacy needs of prospective science teacher students in order to strengthen their capacity to integrate technology into ESD-oriented learning. The study employed a quantitative descriptive survey design, utilizing the Rasch Rating Scale Model, to systematically analyze students' digital literacy competence. A total of 140 second-semester students from two universities completed a 20-item closed-ended questionnaire on a 4-point scale. The results indicated deficiencies in several areas, including information retrieval, scientific writing, participation in digital platforms, collaboration, and digital ethics, often due to the lack of supportive learning models and limited opportunities for real-life application. The findings contribute to science education by providing empirical evidence on specific digital literacy gaps, informing the design of instructional models, training programs, and curriculum innovations to enhance digital literacy for ESD in science education.